2022
DOI: 10.3390/microorganisms10102056
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Bacteria Inhibiting Clostridium perfringens and Assessment of Their Beneficial Effects In Vitro and In Vivo with Whole Genome Sequencing Analysis

Abstract: Various countries and organizations call for banning the use of antibiotic growth promoters (AGPs) as prophylaxis and for growth promotion in the livestock industry. Hence, seeking a substitute for antibiotics is strongly required by the livestock industry to maintain the productivity level and profits. Probiotics could represent one viable solution because of their beneficial effects on host health and maintaining the intestinal microbiota balance. In the present study, we aimed to isolate bacterial strains w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 72 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…Apart from the production of antimicrobial compounds, B. amyloliquefaciens could outcompete C. perfringens for nutrients and other resources within the gut environment. Studies involving murine models have demonstrated that the Ba40 strain was able to outperform C. perfringens by adhering to gut epithelium and proliferating ( Zhao et al 2016 , Jiang et al 2022 ). Additionally, B. amyloliquefaciens stimulates the host's immune response against C. perfringens , reducing the release of pro-inflammatory cytokines ( Zhao et al 2016 , Jiang et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the production of antimicrobial compounds, B. amyloliquefaciens could outcompete C. perfringens for nutrients and other resources within the gut environment. Studies involving murine models have demonstrated that the Ba40 strain was able to outperform C. perfringens by adhering to gut epithelium and proliferating ( Zhao et al 2016 , Jiang et al 2022 ). Additionally, B. amyloliquefaciens stimulates the host's immune response against C. perfringens , reducing the release of pro-inflammatory cytokines ( Zhao et al 2016 , Jiang et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies involving murine models have demonstrated that the Ba40 strain was able to outperform C. perfringens by adhering to gut epithelium and proliferating ( Zhao et al 2016 , Jiang et al 2022 ). Additionally, B. amyloliquefaciens stimulates the host's immune response against C. perfringens , reducing the release of pro-inflammatory cytokines ( Zhao et al 2016 , Jiang et al 2022 ). By producing immunomodulatory compounds such as exopolysaccharides, B. amyloliquefaciens activates the host's immune system, enhancing its resistance to bacterial infections ( Sung et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…To further investigate the possible mechanism on its selenite reduction, the genome-wide analysis was used in this study. Our previous study had shown the genomic characteristics and antibacterial capacity of Bacillus amyloliquefaciens BA40 against Clostridium perfringens (Jiang et al 2022 ). In this study, our analyses indicated that the expression of sugar metabolism, energy metabolism, and selenoprotein metabolism pathway genes played an important role in SR14 fermentation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the positive activity of esterase is related to the breaking activity of the ester bonds of polysaccharides, favoring the action of hydrolases of high molecular weight compounds such as carbohydrates and proteins. Likewise, the positive activity of acid phosphatase is important for the degradation of organic phosphorus found primarily in plant and animal protein sources [43]. In addition to these characteristics, the C33 strain has the possibility of using different energy sources such as glucose, sucrose, maltose, salicin, mannitol, and trehalose, a fact that may favor the fish's nutrition, improving the absorption of nutrients by solubilizing the elements of the diets through extracellular enzymes; this facilitates the absorption of individual molecules through the intestinal epithelium of the animal host [44,45] and provides enzymes that the animal host does not have [44,46].…”
Section: Discussionmentioning
confidence: 99%